Annual review of the sociology of religion. Volume 4, Prayer in religion and spirituality - Giordan, Giuseppe (Leiden : Brill, 2013)
Prayer is a valuable focus for understanding how people interpret themselves, others and the world in which they live. It is a phenomenon which seems to be characteristic not only of participants in every religion, but also men and women who do not identify with traditional religions.
Description based on print version record.
Keywords: Prayer; Spirituality; BODY, MIND & SPIRIT / Inspiration & Personal Growth; BODY, MIND & SPIRIT / Spirituality / General; RELIGION / Christianity / General; RELIGION / Devotional; RELIGION / Spirituality; Electronic books